Estudo da resistência não drenada de solo de baixa consistência por meio de ensaios de campo e laboratório - Lemos, Silvia Gomes Fernandes Polido (2014)
When planning a geotechnical engineering project, it is crucial to know the properties of the soil at the site; this requirement is a complex element of determining the parameters of a geotechnical project because of the the natural variability of the subsoil and the measurement of undrained shear strength is an important parameter for stability analyzes in soft soils. The fall cone test and laboratory vane test, unconventionals, the piezocone and vane tests, in situ, and the unconfined compression test and the unconsolidated undrained triaxial compression test, in laboratory, were used to measure the undrained shear strength of a layer of marine soft clay situated in the Brazilian central coastal plain. Laboratory tests were carried out in undisturbed samples collected with the stationary piston sampler in a vertical near of the field tests. The site was targeted for a campaign of standard penetration tests, with the stratigraphic profile shown through computational modeling. Were also carried out characterization tests (grain-size distribution, density of the grains, moisture content, liquidity and plasticity limits), the identification of the clay minerals using the X-ray diffraction technique and the oedometer consolidation test to obtain the stress history and for evaluating the undisturbed sample quality. The undrained strength values obtained by laboratory tests were compared to the continuous strength profile determined empirically from the piezocone, with the cone factor Nkt calibrated using the field vane test. The results presented good agreement, with the natural variability of the soil prevalent over the quality of the samples in causing the variations observed in the results. The undrained strength values obtained from fall cone and laboratory vane tests were compared, showing good compatibility. Both when compared to field vane test did not show good agreement. The undrained strength values obtained from unconfined compression test and triaxial compression test showed good compatibility with the results of fall cone test, which did not occur with the results of laboratory vane test. The values of the strength normalised with respect to the overconsolidation stress obtained using the various test methods were compared with some empirical correlations reported in the international literature, and agreement was observed with the correlations of Mesri (1975) and Jamiolkowski et al (1985) for clays samples with plasticity index greater than 60%. The unconventional tests showed good reliability, which combined the simplicity and speed of execution, justify the dissemination of these tests in Brazilian geotechnical investigation as an alternative method to complement and support the estimates of undrained shear strength of soft soils.